Pengaruh Polutan Terhadap Struktur Morfologi Stomata Daun Trembesi (Samanea saman (Jacg) Merr) - Pratiwi Dyah Kusumo (Biota, 2017)
Trembesi (Samanea saman) is one of the plants that is currently developed as one of the green line plants. Stomata as part of the leaf that has the ability to bind air, especially oxygen and carbon dioxide, is one part of the plant that can be used as an indicator to see the effect of pollutants contained in the air. The result was obtained by using an electron microscope to analyze the morphological structure of stomata leaves Trembesi (Samanea saman). Location was determined by two groups, the control group was at the UKI campus environment which was away from air pollution and the treatment group was in the Cawang police station where many vehicles passed through. Within a 90 days after treatment of pollutant exposure to plants, the structure of Trembesi leaf stomata was observed using an electron microscope. Based on the observation, the leaf position in the middle of the tree and the position of the leaf at the bottom of the tree, it was found that the leaves placed in the control position had a finer stomata mouth structure, more leaf hairs, and a wider diameter. While on the leaves that are placed on the location exposed to pollutants, has an irregular leaf mouth structure, fewer leaf feathers, and smaller diameter. This study can be concluded that there was an effect of exposure of pollutant that could change morphology of stomata leaves of Trembesi (Samanea saman).